Fathers' parenting behaviors and Malaysian adolescents' anxiety: family income as a moderator - Jafari, Mahboubeh; Baharudin, Rozumah; Archer, Marc (Sage Publications, 2016)
The present study examined the moderating role of family income on the relationships between perceived paternal parenting behavior and adolescents’ anxiety among economically and ethnically diverse sample of adolescents. A total of 1,200 participants aged between 12 and 17 years were selected for the study. A self-administered questionnaire, including Quality of Parenting Behavior Scale and Beck Anxiety Inventory–Malay were used to collect the data. The results obtained indicate that there was a significant relationship between paternal hostility (β = .34, p < .001) and paternal monitoring (β = −.29, p < .01) with adolescents’ anxiety. A multigroup analysis using structural equation modeling also demonstrated that family income level moderated the relationship between parenting and adolescent outcomes. The findings revealed that paternal consistent discipline and paternal monitoring behavior reduced adolescent anxiety in high-income families. Finding advanced understanding on how the associations between fathers’ parenting behaviors and adolescent anxiety could be quite varied when family’s financial circumstances were taken into account.